Fatores associados à ocorrência de lesões faciais em vítimas de acidentes de trânsito periciadas em um instituto forense no nordeste do Brasil - CARVALHO, Joseany Barbosa Laurentino de (2018)
The damages caused by traffic accidents correspond to high emotional, social costs, and especially expenses with health care. Accident injuries occupy a prominent place in the current epidemiological scenario and the facial region corresponds to one of the main sites of injury, and is sometimes responsible for irreparable physical sequelae. They may cause permanent weakness of the masticatory function, aesthetic and phonetic, associated to the permanent physical weakness of the stomatognathic apparatus. The objective of this study was to determine the characteristics associated to traffic accidents with body injuries, analyzing the sociodemographic aspects, body and / or facial region affected and resulting damages, in victims attended at the Institute of Legal Medicine of Teresina, Piauí. This is a cross-sectional study that analyzed 464 reports issued by physicians and odontolegists between april and september 2018. The results showed that the majority of the victims of traffic accidents were males, aged between 30 and 59 years, marital status without partner, and were employed. For these characteristics, there was no significant difference between the groups with and without facial lesion. In addition, in comparative analysis, victims with facial injuries had a higher percentage of fatalities and motor vehicle crashes, and most occurrences were recorded overnight and at night. After multivariate analysis, the data revealed that lesions in the skull, thorax and upper limbs were associated with facial lesions. It was observed that victims with skull lesions are about 5 times more likely to have a lesion on the face. Most of the sample presented soft tissue on the face. It was found that the frontal, orbital, nasal and zygomatic regions were the most affected. Traffic accidents are responsible for high morbidity and mortality, often involving men, unmarried, employed, aged between 30 and 59 years and more likely to involve motorcycles. Facial injuries were associated with fatality, at dawn, and the types of accidents involving motorcycles and automotive are the most common. Thus, it is extremely important to know the profile of the victims and the injuries resulting from these occurrences, in relation to the affected body segment and the associated damages, to treat them well and think about their prevention.